The Loongana (CL) group of carbonaceous chondrites. (1st July 2021) - Metzler, Knut; Hezel, Dominik C.; Barosch, Jens; Wölfer, Elias; Schneider, Jonas M.; Hellmann, Jan L.; Berndt, Jasper; Stracke, Andreas; Gattacceca, Jérôme; Greenwood, Richard C.; Franchi, Ian A.; Burkhardt, Christoph; et al.
Highlights: Five related meteorites define the Loongana (CL) group of carbonaceous chondrites. Coolidge, Loongana 001, LoV 051, NWA 033, and NWA 13400 represent CL chondrites. Strongest depletions of volatile elements in the CL group of carbonaceous chondrites. Unique positions of carbonaceous chondrites of the CL group in a ε 54 Cr- ε 50 Ti diagram. Enrichment of 16 O in some CL chondrites compared to CO, CV, and CK chondrites. Abstract: A coordinated study of the petrology, mineral chemistry, and bulk chemical and isotopic composition of the five ungrouped carbonaceous chondrites Coolidge, Loongana 001, Los Vientos (LoV) 051, Northwest Africa (NWA) 033, and NWA 13400 reveals that these meteorites have a similar set of properties that distinguishes them from the other carbonaceous chondrite groups and allows definition of the new Loongana (CL) group of carbonaceous chondrites. The basic characteristics of the investigated samples are: (1) Lithophile element ratios (e.g., Al/Mg, Si/Mg) are within the typical range of other carbonaceous chondrite groups. (2) Fe-Ni metal abundances are considerably higher than for CV, but similar to CR chondrites. (3) Chondrule size-frequency distributions are similar to CV, but dissimilar to CR chondrites. (4) The mean CAI abundance is ∼1.4 vol%, i.e., lower than in CV but much higher than in CR chondrites. (5) Very low amounts of matrix (17–21 vol%), the lowest among the main carbonaceous chondrite groups (CI, CM, CO, CV, CR, CK). (6) Olivine is nearly equilibrated, with mean fayalite (Fa) values between 12.5 mol% (Loongana 001) and 14.7 mol% (NWA 13400) as a metamorphic effect. (7) Lower Al2 O3 and higher MgO and Cr2 O3 concentrations in matrix, compared to matrix in CV, CK, and CR chondrites. (8) Volatile elements (Mn, Na, K, Rb, Cs, Zn, Se, Te, Pb, Tl) are considerably depleted compared to all other main carbonaceous chondrite groups, reflecting the low matrix abundance. (9) Bulk O isotope compositions plot along the CCAM line (Δ 17 O −3.96 to −5.47‰), partly overlapping with the CV and CK chondrite fields but including samples that are more 16 O-rich. (10) Unique positions of CL values in the є 54 Cr-є 50 Ti isotope plot, with є 54 Cr values similar to CV, CK, and CO, but є 50 Ti values similar to CR chondrites. All CL chondrites studied here are of petrologic type 3.9 to 4, indicating that they have been thermally metamorphosed on the parent body. The diagnostic features of CL chondrites detailed here provide a basis for identifying CL members of lower petrologic types. Such samples will be important for determining the pristine state of these meteorites and their components.